Comprehensive analysis of school-related injuries: a global perspective - Che Rani, Nur Farahana; Ruslan, Rusila (IIUM Press, 2024)
Background: Injuries among school children globally pose significant concerns, attributed to a myriad of factors including gender differences, environmental risks, and behavioural patterns. This comparative analysis delves into the prevalence of school-related injuries across nations, highlighting disparities and underscoring the necessity for tailored safety measures. Notably, boys exhibit higher vulnerability due to their propensity for active behaviour and engagement in physical activities, with common injury sites identified as playgrounds and classrooms. Methods: The research methodology employed a meticulous approach, selecting pertinent articles from databases such as IIUM, Proquest, Pubmed, ResearchGate, and Science Direct. From an initial pool of 879 articles, 14 were identified through systematic screening, focusing on aspects related to the knowledge, attitude, and practice of first aid. This selection process ensured a targeted exploration of relevant literature, providing insights into injury management strategies within school settings. Results: Findings reveal the urgent need for enhanced safety protocols within schools, particularly in regions like Malaysia where injuries rank as a leading cause of morbidity and mortality among children. The comparative analysis across low-and middle-income countries further elucidates variations in hospital admission rates for addressing unintentional injuries in children, highlighting the importance of context-specific interventions. Conclusion: In conclusion, safeguarding the well-being of school children necessitates a holistic approach that addresses both individual behavior and environmental factors. Robust safety measures, informed by comprehensive research and tailored to specific contexts, are imperative for creating safer learning environments during the critical developmental years of children. Through proactive initiatives and collaboration between educators, policymakers, and healthcare professionals, the goal of mitigating injury incidence and promoting overall child health and well-being can be achieved.